PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS DISCOVERY LEARNING PADA MATERI EKOLOGI KELAS X SMA - Pratiwi, Mia Utari; Arnentis, Arnentis; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aims to develop the Student Worksheet (LKPD) based on discovery learning for senior high school grade X of the topic of ecology in May-July 2020. The research was conducted in two places, namely to Student Worksheet validation was conducted at the FKIP UNRI Biology Education Campus and Student Worksheet limited trials were conducted at SMAN 8 Pekanbaru. This type of research refers to the R&D research approach using the ADDIE model developed by Dick and Carry. The subject of this research is the subject matter of Biology in senior high school grade X KD 3.10. The developed LKPD consisted of 3 meetings with a time allocation of 1 meeting for 45 minutes. The parameters of this study include the results of the validation of the development of student worksheet by the validator and respon assesment by student. The assessment is doing with validation sheet and a questionnaire. Data analysis is descriptive qualitative and quantitative. The results of this study indicate that student worksheet that have been developed are in the very valid category with an average score of all aspects of 3.52. The value of the answers to all aspects the value of the results of a limited trial phase I and stage II in all aspects obtained an average score of 3.65 with a very good category. Based on the results of the validation, the results of the first trial, the results of the second trial and the revisions that have been made, student worksheet is good and feasible to be used as a reference at school learning to increase students knowledge and understanding for the topic of ecology.Key Words: Student Worksheets, Discovery Learning, EcologyPENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS DISCOVERY LEARNING PADA MATERI EKOLOGI KELAS X SMA